Specifying Concurrent Controller of Production Cell Using the Notation of Shared State and Events of Duration Calculus - Md. Aminuddin, Rusdi; Jifeng, He; Abdullah, Rosni (Malaysian Journal of Computer Science, 2001)
This report presents a method to specify a set of controllers for a Robotics production cell using the Duration Calculus. The case study is adopted from a report by Claus Leverentz on specifying a real metal processing plant in Karlsruhe using other formal and semi-formal methods. Our contribution to this case study aims at illustrating the methodology associated with the concept of shared state model and events for describing and specifying synchronised controllers. We use the notion of state to describe and model the sensors and actuators. Next, we apply the leads-to operator to list the assumptions which are aspects of the behaviour of the plant that cannot be controlled by the controllers. We then show how one can specify each controller using leads-to and state notation as shared variables for synchronising the interaction of the controllers. Specification are structured modularly according to the physical structure of the system.